1997
DOI: 10.1128/jb.179.8.2608-2615.1997
|View full text |Cite
|
Sign up to set email alerts
|

Open reading frame 3, which is adjacent to the mycocerosic acid synthase gene, is expressed as an acyl coenzyme A synthase in Mycobacterium bovis BCG

Abstract: The aim of this study was to test for expression of a 900-bp open reading frame (ORF), ORF3, located at the 5 end of the mycocerosic acid synthase gene in Mycobacterium bovis BCG and to determine the nature of the ORF3 protein. ORF3 was expressed as a 61-kDa C-terminal fusion protein with glutathione S-transferase in Escherichia coli. Polyclonal rabbit antiserum, prepared against this fusion protein, cross-reacted with a 65-kDa protein in M. bovis BCG crude extracts. Since this protein was larger than that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
(31 reference statements)
0
23
0
Order By: Relevance
“…However, in vitro studies indicated that purified ACoAS protein catalyzed the activation of mycocerosic acids to their corresponding thioesters only at extremely low rates. Furthermore, ACoAS failed to stimulate MAS activity and did not cause measurable release of mycocerosic acids either in the free form or as phthiocerol derivatives when phenolphthiocerol or glycosylated phenolphthiocerol was provided as acceptor (11). Although such in vitro reconstitution experiments failed to reveal the function of ACoAS, additional factors may be necessary for this protein to function in the transfer of mycocerosic acids to the diol acceptors.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…However, in vitro studies indicated that purified ACoAS protein catalyzed the activation of mycocerosic acids to their corresponding thioesters only at extremely low rates. Furthermore, ACoAS failed to stimulate MAS activity and did not cause measurable release of mycocerosic acids either in the free form or as phthiocerol derivatives when phenolphthiocerol or glycosylated phenolphthiocerol was provided as acceptor (11). Although such in vitro reconstitution experiments failed to reveal the function of ACoAS, additional factors may be necessary for this protein to function in the transfer of mycocerosic acids to the diol acceptors.…”
mentioning
confidence: 81%
“…This laboratory has previously cloned and characterized the mycocerosic acid synthase gene (mas) (9) and has identified a gene cluster involved in phthiocerol and phenolphthiocerol synthesis (pps) in Mycobacterium bovis BCG (10). In addition, we recently reported that a small open reading frame, ORF3, is located at the 5Ј end of the mas gene; amino acid sequence homology and enzyme assays using purified ORF3 protein indicated that this open reading frame encoded an ACoAS 1 (11). Genes homologous to acoas have been identified adjacent to the mas gene in M. tuberculosis (GenBank TM accession number Z83858) and Mycobacterium leprae (GenBank TM accession number U00010), as well as 5Ј to a polyketide synthase gene and 3Ј to a mas-like gene in M. tuberculosis (GenBank TM accession numbers Z74697, U00024, and Z77826).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 65 kDa protein isolated from this extract by immunoaffinity purification with the antibodies showed acyl-CoA synthase activity. In view of the presence of the orf3 gene in close proximity to mas, a pks and a mas-like gene in several mycobacterial species, it is tempting to suggest that the products of the orf3-like genes function selectively with the products of the neighbouring synthase genes, presumably to transfer the synthase products to their biochemical acceptors (Fitzmaurice and Kolattukudy, 1997). Thus, for example, the ORF3 protein could either activate mycocerosic acids or function with a membrane-localized protein to transfer mycocerosyl groups from the synthase to the diols.…”
Section: Biosynthesis Of Methyl-branched Fatty Acidsmentioning
confidence: 99%
“…21 52 The biosynthesis of PDIMs and PGLs has been a subject of intensive studies in recent years, 52 pioneered by Kolattukudy and co-workers. 53,54 The role of PDIMs and PGLs in virulence has now been well established. 52,55 Both of these molecules are thought to play a role in modulation of the host immune response.…”
Section: Bcg: a Brief Historymentioning
confidence: 99%